Internalization of Huma Betang Cultural Values through Narrative Counseling for Elementary Education Students - Sunaryo Alidha Sunaryo; Fendahapsari Singgih Sendayu; Aldo Redho Syam (Universitas Muhammadiyah Ponorogo, 2021)
The Dayak people in the city of Palangka Raya have made the philosophy of “huma betang” culture as a cultural value that regulates life together with the community with the understanding “where the earth is set, the sky is upheld there”. This “huma betang” culture also gives meaning to the Dayak people to be able to respect the customs that apply in their environment, so that it is hoped that it can create a safe and peaceful condition in the city of Palangka Raya without division and conflict. This study uses a qualitative research method with a gadamerian hermeneutic approach to interpreting the internalization of the values of “huma betang” cultural through narrative counseling, both symbolic, linguistic and non-linguistic for basic education students in the city of Palangka Raya. This study resulted in the finding that the internalization of “huma betang” cultural values through a narrative counseling approach for primary education students in Palangka Raya city consists of values of honesty, togetherness, kinship, mutual cooperation, and tolerance. The internalization of “huma betang” cultural values that have been carried out by counselors for basic education students in the city of Palangka Raya has been able to help students experience changes in self-understanding and openness through the use of students’ language or the actions they take to solve the problems they experience.